Macropinocytosis and autophagy crosstalk in nutrient scavenging. (17th December 2018) - Florey, Oliver; Overholtzer, Michael
Abstract : Adaptive strategies used by cells to scavenge and recycle essential nutrients are important for survival in nutrient-depleted environments such as cancer tissues. Autophagy and macropinocytosis are two major mechanisms that promote nutrient recycling and scavenging, which share considerable, yet poorly understood, cross-regulation. Here we review recent findings that connect these starvation response mechanisms and discuss the implications of their crosstalk. This article is part of the Theo Murphy meeting issue 'Macropinocytosis'.